Indonesian Female Police Officer’s Deployment as International Police Officers in United Nations – African Union Mission in Darfur (UNAMID) (2016-2018) - Witri Elvianti; Meilisa Rusli (Journal of Islamic World and Politics, 2021)
The main purpose is to analyze the role of Indonesian female police deployed as Individual Police Officers in the United Nations peacekeeping operation in Darfur from 2016 to 2018. This research was designed as a qualitative case study that triangulated data from previously published researches, institutional documents, and semi-structured qualitative interviews. Previous scholarly publications were used to observe gender deficit – which is the lack of female personnel in UN peacekeeping missions. Institutional documents, particularly ex-Indonesian female police reports, were analyzed to contribute to data enrichment in this research. Lastly, the authors conducted semi-structured qualitative interviews with some ex-female police who have completed their deployment in UNAMID (2016-2018). Concerning the gender equality and counterinsurgency concepts, this research figured out that Indonesian female police could demonstrate their strategic role to provide skill-building activities, trust-building with refugees, and human rights advocacy. The numbers of Indonesian female police in this mission remained higher than other Southeast Asian contributing countries, but the Indonesian female police were also functional in line with the UN gendering peace and security agenda.